Circularized and Corner-Rounded Rectangular Reinforced Concrete Columns Wrapped with CFRP Under Eccentric Compression - Dang, Tung D.; Nguyen, Canh Tuan; Cao, Vui Van (Civil Engineering Journal, 2025)
This paper presents experimental and analytical investigations on the behavior and mechanical properties of carbon fiber reinforced polymer (CFRP) confined circularized and corner-rounded rectangular reinforced concrete (RC) columns under eccentric loading. Twelve RC columns with cross sections of 150×200 mm were tested. Two columns were used as control specimens. Five columns were circularized and then wrapped with five CFRP configurations. The other five columns were corner-rounded and then wrapped with the above configurations. These twelve columns were eccentrically loaded until they failed. The results indicated that CFRP-confined circularized RC columns failed by CFRP rupture at the eccentric side, while CFRP-confined corner-rounded RC columns failed by CFRP rupture localized at corners. The outstanding effectiveness of the circularization method was its increase in the ultimate load of CFRP-confined circularized RC columns by 3.0–4.3 times that of the control columns. In contrast, the corner-rounding method moderately increased the ultimate load of CFRP-confined corner-rounded RC columns by 1.3–1.7 times that of the control columns. The circularization method outstandingly improved the elastic stiffness by 273.9%–419.3% compared with that of control columns, whereas the corner-rounding method exhibited no effect on the elastic stiffness. The rotation ductility of CFRP-confined circularized and corner-rounded RC columns significantly improved to high ductility when confined with more than 1.33 CFRP layers. Theoretical analyses were performed, and simple models were proposed for reasonably estimating the ultimate loads of the CFRP-confined circularized and corner-rounded RC columns under eccentric loading.